2010
DOI: 10.1021/la102303q
|View full text |Cite
|
Sign up to set email alerts
|

Universal Surfactant for Water, Oils, and CO2

Abstract: A trichain anionic surfactant sodium 1,4-bis(neopentyloxy)-3-(neopentyloxycarbonyl)-1,4-dioxobutane-2-sulfonate (TC14) is shown to aggregate in three different types of solvent: water, heptane, and liquid CO(2). Small-angle neutron scattering (SANS) has been used to characterize the surfactant aggregates in water, heptane, and dense CO(2). Surface tension measurements, and analyses, show that the addition of a third branched chain to the surfactant structural template is critical for sufficiently lowering the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
99
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 32 publications
11
99
0
1
Order By: Relevance
“…Hence, the data for these two surfactants are not included in the phase diagram. Earlier studies on the identical system also reported the inability of the AOT14 surfactant to stabilise w/c microemulsions [42] despite the versatility of the parent AOT14; which is the TC14 surfactant, in a wide range of solvent [41,49]. However, changing the hydrophilic headgroup into the larger sulfoglutarate was not sufficient to increase the tendency of the surfactants to stabilize w/c microemulsions.…”
Section: High-pressure Phase Behaviourmentioning
confidence: 97%
“…Hence, the data for these two surfactants are not included in the phase diagram. Earlier studies on the identical system also reported the inability of the AOT14 surfactant to stabilise w/c microemulsions [42] despite the versatility of the parent AOT14; which is the TC14 surfactant, in a wide range of solvent [41,49]. However, changing the hydrophilic headgroup into the larger sulfoglutarate was not sufficient to increase the tendency of the surfactants to stabilize w/c microemulsions.…”
Section: High-pressure Phase Behaviourmentioning
confidence: 97%
“…In water, however, the hydrophobic nature of graphene leads to the agglomeration of graphene sheets into graphitic layered structures or agglomerates, thus spontaneous wetting by water is theoretically impossible. It has long been established in colloid science that to achieve a thermodynamically stable dispersion of one phase in another requires the lowering the interfacial energy between two immiscible phases, using surfactants that either strongly bind to the target compound or are solvated by the continuous phase [87][88][89]. However, very little is known as to whether graphene dispersions can be thermodynamically stable [90].…”
Section: Graphene-compatible Surfactantsmentioning
confidence: 99%
“…Interestingly, this research showed that the stability of this mixed colloidal system can be dramatically enhanced via the introduction of a third, highly branched hydrocarbon and methylated chain, i.e. TC14 surfactant (sodium 1,4-bis(neopentyloxy)-3-(neopentyloxycarbonyl)-1,4-dioxobutane-2-sulphonate) ( Table 1) [22]. The addition of this tri-chain surfactant is generally believed to efficiently lower the surface energy and packing requirements of a surfactant at the CO 2 -water interface [22].…”
Section: Introductionmentioning
confidence: 99%
“…TC14 surfactant (sodium 1,4-bis(neopentyloxy)-3-(neopentyloxycarbonyl)-1,4-dioxobutane-2-sulphonate) ( Table 1) [22]. The addition of this tri-chain surfactant is generally believed to efficiently lower the surface energy and packing requirements of a surfactant at the CO 2 -water interface [22]. Interestingly, this feature precisely seemed to control MWCNT dispersibility in polymer matrix [20,23,24].…”
Section: Introductionmentioning
confidence: 99%